Peran Guru Dalam Pembelajaran - Siti Nurzannah (LPPPI Publishing, 2022)
Teachers are the most important factor in advancing education. This paper aims to outline the role of teachers in learning. This paper uses the literature method by analyzing books and journals related to the theme of discussion. The results of this study show that the task of the teacher as a motivator is to increase the passion and enthusiasm for learning students both by giving motivational words and certain tasks that will arouse their curiosity. Meanwhile, the task of the teacher as a facilitator is not only a matter of physique or infrastructure, even this is a school task, but how the teacher facilitates the mentality of students in learning and provides the widest opportunity for students to ask questions, discuss and so on.